Problems of economic union - Meade, J. E. (Chicago : University of Chicago Press, 1953)
This book is based upon three lectures on problems connected with the formation of economic unions between sovereign states in the conditions of the modern world.
osc 25/10/2018
Loans
Keywords: Commercial policy; Balance of trade; International cooperation